Dari Domestik Hingga Publik: Aktivitas Produksi dan Reproduksi Sosial Buruh Perempuan PTPN X Pecoro Jember - Alfan Jamil Efendi (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This study examines the dynamics of production and social reproduction among female tobacco warehouse workers at PTPN X Pecoro, Jember Regency. Women workers hold dual roles as paid laborers in the production sphere and as primary actors in unpaid domestic work. This research aims to describe and analyze the production and social reproduction activities experienced by female workers at PTPN X Pecoro. Using a qualitative ethnographic approach, data were collected through in-depth interviews, participant observation, and documentation, then analyzed using Social Reproduction Theory (SRT) by Tithi Bhattacharya. The findings show that women play a central role in sustaining both economic production and household life. Besides performing labor-intensive work in the warehouse, they continue unpaid domestic responsibilities such as childcare and household tasks, creating a double burden. Despite economic and structural limitations, women develop adaptive strategies through social networks and collective support. This study concludes that production and social reproduction are closely interconnected, while reproductive labor often remains invisible within agrarian-industrial contexts.
:: Finalisasi file repositori 28 Juli 2026_Kurnadi
Keywords: Double burden; female workers; social reproduction.